6. Mental Health, Burnout and Stress-Related Symptoms Among Youth: Prevalence and Pandemic Effects - Kuterovac Jagodić, Gordana; Maslić Seršić, Darja; Antulić Majcen, Sandra (Two Countries, One Crisis: The YO-VID22 Pandemic Study, 2025)
The chapter examines youth mental health in Croatia and Slovenia through validated measures of depression, anxiety, stress (DASS-9), burnout (BAT-12), and self-reported worries. Results indicate elevated levels of impairment, with over one-quarter of young people in both countries reporting severe depressive symptoms, around 20% reporting severe anxiety, and nearly one-third reporting high stress, with Croatian respondents consistently showing slightly higher levels of depression and stress. Burnout symptoms were more pronounced among students than employed youth, which underlines the role of educational settings as environments of heightened psychological strain. There were statistically significant gender and age disparities observed: young women, particularly in the youngest cohorts, reported the highest levels of mental health difficulties, whereas older women showed improvement. Among men, different age-related trends emerged. Socio-economic status also influenced outcomes, with financially better-off youth reporting fewer symptoms.